Financial Ratio Analysis to Improve Village Government Financial Performance: Case Study on the Sarang Burung Village Government, Jambi Luar Kota District, Muaro Jambi Regency - Sherly Sarlina; Sri Rahayu; Netty Herawaty (Harmony Management: International Journal of Management Science and Business, 2025)
The purpose of this study is to evaluate the Sarang Burung Village Government's financial performance for the fiscal year 2020–2023 in the Jambi Luar Kota District of the Muaro Jambi Regency. Six financial ratios—the Degree of Decentralization Ratio, Village Financial Independence Ratio, Village Financial Dependency Ratio, PADes Effectiveness Ratio, Expenditure Efficiency Ratio, and Revenue Growth Ratio—will be used in this study to examine Sarang Burung Village's financial performance. The Realization Report of the Village Revenue and Expenditure Budget (APBDes) of Sarang Burung Village, Jambi Luar Kota District, Muaro Jambi Regency, for the fiscal years 2020–2023 is the source of secondary data used in this quantitative descriptive study. The study's findings indicate that the Sarang Burung Village Government's financial performance is classified as extremely poor based on the Degree of Decentralization Ratio, very low for the Village Financial Independence Ratio, very high for the Village Financial Dependency Ratio, ineffective for the PADes Effectiveness Ratio, less efficient for the Spending Efficiency Ratio, and not good for the PADes Growth Ratio. The SWOT Analysis employs the S-T strategy, which leverages internal strengths to counter external threats.